2020
DOI: 10.2174/1871520620666200424112504
|View full text |Cite
|
Sign up to set email alerts
|

Zidovudine Glycosylation by Filamentous Fungi Leads to a Better Redox Stability and Improved Cytotoxicity in B16F10 Murine Melanoma Cells

Abstract: Background: The strategic development of therapeutic agents capable of being targeted at their active sites has been a major goal in the treatment of cancer. The delivery of drugs for tumors has as its main challenge the development of safe and effective drugs, since the goal of chemotherapy is to eliminate the tumor completely without reaching healthy cells. The aim of the present study was to investigate the antioxidant, anticancer activitie of zidovudine and its α-O-glycosylated derivative obtained by bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…C. blakesleeana and C. echinulata are two species that are often used in xenobiotic biotransformation studies [ 4 , 10 , 15 ], and both grow as biofilms if cultivated in the same manner as C. elegans , i.e., in an Erlenmeyer flask containing a steel spring. To determine what, if any, potential signalling molecules are produced by these fungi, supernatants from 120 ​h planktonic and biofilm cultures were extracted with ethyl acetate, and the extracts analysed by GC-MS.…”
Section: Resultsmentioning
confidence: 99%
“…C. blakesleeana and C. echinulata are two species that are often used in xenobiotic biotransformation studies [ 4 , 10 , 15 ], and both grow as biofilms if cultivated in the same manner as C. elegans , i.e., in an Erlenmeyer flask containing a steel spring. To determine what, if any, potential signalling molecules are produced by these fungi, supernatants from 120 ​h planktonic and biofilm cultures were extracted with ethyl acetate, and the extracts analysed by GC-MS.…”
Section: Resultsmentioning
confidence: 99%
“…Differential glycosylation patterns on the drug could lead to size and charge heterogeneity and may affect ultimate therapeutic effect. Arruda et al also found that Zidovudine glycosylation patterns affected its efficacy on melanoma [11].…”
Section: Glycosylating Pharmaceuticals For Delivery Improvementmentioning
confidence: 95%
“…Palavras chaves: Antioxidantes; Quimioinformática; Análise multivariada; Conservantes Farmacêuticos drug, foodstuff and cosmetics (ARRUDA et al, 2020;MOREIRA et al, 2022;NAGARAJAN et al, 2020).…”
Section: Introductionunclassified